CTNI-38. PriCoTTF TRIAL: A PHASE I/II TRIAL OF TTFIELDS PRIOR AND CONCOMITANT TO RADIOTHERAPY IN NEWLY DIAGNOSED GLIOBLASTOMA. (12th November 2021) - Kebir, Sied; Pierscianek, Daniela; Proescholdt, Martin; Hau, Peter; Grosu, Anca-Ligia; Krex, Dietmar; Sure, Ulrich; Scheffler, Björn; Stuschke, Martin; Glas, Martin
Abstract: TTFields therapy is applied at 200 kHz by arrays that are placed at the patients' scalp. In the phase 3 EF-14 trial, survival rates were significantly improved when adding tumor-treating fields (TTFields) to adjuvant temozolomide-based chemotherapy in patients with newly diagnosed glioblastoma (nGBM). Preclinical studies showed that combination of TTFields and radiotherapy synergistically impaired glioblastoma cell growth. Here, we present the PriCoTTF trial, which is enrolling nGBM patients and will assess the safety and efficacy of TTFields initiated prior and concomitant to radiochemotherapy. Following surgery and wound-healing, TTFields therapy is initiated in adult nGBM patients. TTFields therapy continues throughout radiochemotherapy and adjuvant chemotherapy for a total of approximately 9 months. During radiotherapy, the arrays - through which TTFields is delivered - remain on the patients' scalp. Totally, thirty-three patients are planned to be enrolled in two treatment arms. In arm A, 20 patients receive normo-fractionated radiotherapy, whereas in the elderly arm, arm B, 13 patients receive hypo-fractionated radiotherapy. The primary endpoint of this trial is safety and tolerance that will be gauged by a set of pre-specified treatment-limiting toxicities. Secondary endpoints include the frequency of adverse events, progression-free survival (PFS), and overall survival (OS). The trial is currently enrolling patients at four sites in Germany. At the time of abstract submission, 9 patients enrolled in Arm B. Patient recruitment for arm A has been completed with. We will present initial practical experiences as well as preliminary safety and tolerance data. There is a biological rationale for combining TTFields and radiotherapy to further improve survival of GBM patients. In the presented phase I/II trial, the safety and efficacy of TTFields initiated prior and concomitant to RT in nGBM will be assessed. In addition, initial efficacy data (phase II) may serve as a rationale for a putative randomized phase III trial.